Which Type of Energy Consumption is Effective on Economic Growth? Industry or Residential? The Case of Nuts-2 Regions in Turkiye - Turkmen, Adem; Yarbasi, Ikram Yusuf (International Journal of Energy Economics and Policy, 2023)
This study aims to determine the causal relationship between energy consumption and growth at the regional level, considering energy use's production and consumption purpose. In this direction, the relationship between industrial and residential electricity consumption and economic growth in Turkey has been tested for 26 regions and the period 2007-2020 by the Kónya Bootstrap Panel Causality Approach. According to the analysis results, while 11 areas support the growth hypothesis in terms of industrial electricity consumption, only one shows a bidirectional relationship; that is, it gives results by the feedback hypothesis. Five regions support the growth hypothesis regarding residential electricity consumption, and only two show a bidirectional relationship. In addition, four areas that do not offer a bidirectional relationship have findings that support the conservation hypothesis. According to the results, using energy as an input in final consumption or production may cause different regional effects on growth. Considering these relations, especially when choosing regional development and energy policies, will bring the right results specific to the regions. In addition, the absence of a causal relationship between electricity consumption and growth in many of the 26 areas examined indicates regional problems in the efficient use of resources.